Characteristics of Interpersonal Communication in the Al-Quran with Islamic Boarding School Effectiveness Leadership - Kartini Kartini; Riski Febri Yanti; Iyen Supit; Dea Amanda; Fauziyah Siregar (Penerbit Jurnal Indonesia, 2022)
This study examines the essential ideas of relational correspondence in pesantren that are applicable to the authority style of pesantren and dissects the qualities and shortcomings of relational correspondence in beating hierarchical clash in pesantren to increment authoritative viability. This exploration utilizes a methodology approach with research and logical cycles not generally so straightforward as in quantitative examination, on the grounds that before the aftereffects of subjective examination add to science, the phases of subjective exploration go past the phases of basic logical reasoning, so an analyst is to catch different realities or peculiarities. . The aftereffects of this study demonstrate that (1) the capabilities of the pesantren initiative incorporate the person, the pioneer's job and the contact job, empowering the foundation of a viable correspondence framework; (2). the most common way of sending messages or data from custodians, utilizing correspondence standards and standards in view of the Qur'an and Hadith.